Long-term use of everolimus as a component of immunosuppressive therapy in liver transplant recipients - M. Sh Khubutia; V. E. Sjutkin; N. K. Kuznetsova; S. V. Zhuravel; M. S. Novruzbekov (Трансплантология (Москва))
This article presents a three-year experience with mTOR inhibitors in the schemes of immunosuppressive therapy in patients post liver transplantation.